Analisis Semiotika Roland Barthes Pada Lirik Lagu "Pain Remain I : Dancing Like Flames" Karya Lorna Shore : Roland Barthes Semiotic Analysis of The Lyrics of The Song "Pain Remain I : Dancing Like Flames" by Lorna Shore - Muhammad Suardi; Yeni Ernawati (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study analyzes the meaning of the lyrics of the song “Pain Remains I: Dancing Like Flames” by Lorna Shore using Roland Barthes’ semiotic approach. The main focus of the research is to describe the denotative, connotative, and mythological meanings contained in the song lyrics. This qualitative study employs data collection techniques including documentation, audio-visual materials, and field notes. The analysis results demonstrate that the song lyrics are rich with literal meanings, symbolic expressions, and ideological narratives that are unconsciously accepted by society as truth. The findings strengthen the relevance of Barthes’ theory in deconstructing the structure of meaning in modern music lyrics, especially within the deathcore genre, and broaden the discourse on interpreting lyrics as a medium of emotional and cultural communication.